Research on the Seed Respiration CO2 Detection System Based on TDLAS Technology - Gao, Lu; Zang, Ying; Zhao, Guangwu; Qi, Hengnian; Tang, Qizhe; Liu, Qingshan; Jia, Liangquan (International Journal of Optics, 2023)
The traditional detection method of CO2 concentration in seed respiration has defects such as low detection accuracy, low detection efficiency, and inability to monitor in real time. In order to solve these problems, we report a seed respiration CO2 detection system based on wavelength modulation spectroscopy (WMS) techniques in tunable diode laser absorption spectroscopy (TDLAS). This system uses a 2004 nm distributed feedback (DFB) laser as the light source, and a double-layer seed respiration device (about 1.5 L) is designed based on Herriott cell with an effective optical path of about 21 meters. Then, the second harmonic (2f) signal is extracted by the wavelength modulation method for CO2 concentration inversion. When the ambient temperature and pressure changes greatly, the corrected 2f signal is used for CO2 concentration inversion to improve the accuracy. A series of verification and comparison experiments have proved that the seed respiration CO2 detection system has the advantages of strong stability, high sampling frequency, and high detection accuracy. Finally, we used the developed system to measure the respiration intensity and respiration rate of 1 g corn seeds. The respiration intensity curves and respiration rate change details show that the seed respiration CO2 detection system is more suitable for a small amount of seeds than nondispersive infrared (NDIR) CO2 sensor and gas chromatography in real-time monitoring of the breathing process.